From cellular lysis to microarray detection, an integrated thermoplastic elastomer (TPE) point of care Lab on a Disc. Issue 2 (11th November 2014) - Roy, Emmanuel; Stewart, Gale; Mounier, Maxence; Malic, Lidija; Peytavi, Régis; Clime, Liviu; Madou, Marc; Bossinot, Maurice; Bergeron, Michel G.; Veres, Teodor
Abstract : We present an all-thermoplastic integrated sample-to-answer centrifugal microfluidic Lab-on-Disc system (LoD) for nucleic acid analysis. Abstract : We present an all-thermoplastic integrated sample-to-answer centrifugal microfluidic Lab-on-Disc system (LoD) for nucleic acid analysis. The proposed CD system and engineered platform were employed for analysis of Bacillus atrophaeus subsp. globigii spores. The complete assay comprised cellular lysis, polymerase chain reaction (PCR) amplification, amplicon digestion, and microarray hybridization on a plastic support. The fluidic robustness and operating efficiency of the assay were ensured through analytical optimization of microfluidic tools enabling beneficial implementation of capillary valves and accurate control of all flow timing procedures. The assay reliability was further improved through the development of two novel microfluidic strategies for reagents mixing and flow delay on the CD platform. In order to bridge the gap between the proof-of-concept LoD and production prototype demonstration, low-cost thermoplastic elastomer (TPE) was selected as the material for CD fabrication and assembly, allowing the use of both, high quality hot-embossing and injection molding processes. Additionally, the low-temperature and pressure-free assembly and bonding properties of TPE material offer a pertinent solution for simple and efficient loading and storage of reagents and other on-board components. This feature was demonstrated through integration and conditioning of microbeads, magnetic discs, dried DNA buffer reagents and spotted DNA array inserts. Furthermore, all microfluidic functions and plastic parts were designed according to the current injection mold-making knowledge for industrialization purposes. Therefore, the current work highlights a seamless strategy that promotes a feasible path for the transfer from prototype toward realistic industrialization. This work aims to establish the full potential for TPE-based centrifugal system as a mainstream microfluidic diagnostic platform for clinical diagnosis, water and food safety, and other molecular diagnostic applications.